Fast disease progression in simian HIV-infected female macaque is accompanied by a robust local inflammatory innate immune and microbial response. (19th June 2015) - Ren, Wuze; Ma, Yingfei; Yang, Liying; Gettie, Agegnehu; Salas, January; Russell, Kasi; Blanchard, James; Davidow, Amy; Pei, Zhiheng; Chang, Theresa L.; Cheng-Mayer, Cecilia
Abstract : Objective: Gender differences in immune response and the rate of disease progression in HIV-infected individuals have been reported but the underlying mechanism remains unclear, in part because of the lack of relevant animal models. Here, we report a novel nonhuman primate model for investigation of sex disparity in HIV disease progression. Design/methods: Viral load and rate of disease progression were evaluated in rhesus macaques infected intrarectally with lineage-related subtype C R5 simian HIVs. Cytokine/chemokine levels in rectal swab eluates, and bacterial species adherent to the swabs and in the feces were determined. Results: Simian HIV-infected female rhesus macaques progressed faster to AIDS than male macaques, recapitulating the sex bias in HIV-1 disease in humans. There were no significant differences in the levels of soluble immune mediators in the rectal mucosa of naive female and male macaques. However, an exploratory longitudinal study in six infected macaques indicates that the female macaques mounted an earlier and more robust proinflammatory skewed rectal immune response to infection. Moreover, expansion of Proteobacteria that increase in other intestinal inflammatory disorders was significantly higher in the rectal mucosa of female than male macaques during acute infection. Conclusion: These findings suggest that sex differences in local innate immune activation and compositional shifts in the gut microbiota could be the drivers of increased disease susceptibility in female macaques. Further studies with this novel nonhuman primate model of HIV infection could lead to innovative research on gender differences, which may have important therapeutic implications for controlling disease in infected men as well as women. Abstract : Supplemental Digital Content is available in the text